Simulation of Earthquake Rupture Dynamics in Complex Geometries Using Coupled Finite Difference and Finite Volume Methods (Communications in Computational Physics, 2020)
We couple a node-centered finite volume method to a high order finite differencemethod to simulate dynamic earthquake ruptures along nonplanar faults intwo dimensions. The finite volume method is implemented on an unstructured mesh,providing the ability to handle complex geometries. The geometric complexities arelimited to a small portion of the overall domain and elsewhere the high order finite differencemethod is used, enhancing efficiency. Both the finite volume and finite differencemethods are in summation-by-parts form. Interface conditions coupling the numericalsolution across physical interfaces like faults, and computational ones betweenstructured and unstructured meshes, are enforced weakly using the simultaneous-approximation-termtechnique. The fault interface condition, or friction law, providesa nonlinear relation between fields on the two sides of the fault, and allows for the particlevelocity field to be discontinuous across it. Stability is proved by deriving energyestimates; stability, accuracy, and efficiency of the hybrid method are confirmed withseveral computational experiments. The capabilities of the method are demonstratedby simulating an earthquake rupture propagating along the margins of a volcanic plug.